Clinical Correlative Study Of Posterior Segment Pathology In Blunt Ocular Trauma Using B-Scan Ultrasound (International Journal of Scientific Research and Management (IJSRM), 2015)
Ocular trauma is a major cause of worldwide visual impairment. It is the single most important cause of mono ocular blindness worldwide the effect of which is not only on the career and future of the individual but also on the entire family dependent on that earning individual. Worldwide approximately 55 million eye injuries are believed to occur yearly, leaving 1.6 million eyes blind.